The rise and fall of executive functions in high-level football players. (July 2020) - Beavan, Adam; Spielmann, Jan; Mayer, Jan; Skorski, Sabrina; Meyer, Tim; Fransen, Job
Abstract: Introduction: Executive functions are higher-level cognitive functions. Despite being relevant to many aspects of everyday life, it is contentious whether executive functions are important for high performing athletes. Executive functions increase throughout the career of an athlete, yet it remains unknown what are the main contributors. Therefore, this study examined the effect of age and experience on executive functions in a cohort of high performing football players. Methods: Data were collected over three seasons, resulting in a mixed longitudinal sample of 1018 observations in 343 male players (1–5 observations/player, age: 10.34–34.72 years; playing experience: 5–22 years) from the U12-Senior age groups of a professional German football club. Players participated in four cognitive tasks aimed at measuring higher-level cognitive functioning: a precued choice reaction-time task, a stop-signal reaction-time task, a sustained attention task, and a multiple-object tracking task, from which a total of eight dependent variables related to response time and/or accuracy were derived. Results: Linear and non-linear mixed effects regressions were used to investigate the relationship between age, experience and executive functions. A second order polynomial revealed that, generally, a negatively accelerated curve best described the relationship between age, experience and executive functions. An increasingly smaller difference in executive functioning was generally observed between subsequent age groups, with a performance plateau evident around adulthood ( 21 years old). Age and experience only explained a very low to moderate proportion of the variance in executive functions (marginal explained variance ranged between 2 and 57%). A significant age by field position interaction effect was only observed for the sustained attention task's accuracy and response time components (p < 0.001). Conclusions: Both age and experience showed a negatively accelerated relationship with executive functions in youth football players, and this relationship was generally field position-independent. These negatively accelerated curves seem to reflect those observed in general populations, where a plateau phase in the development of higher-level cognitive functioning is also observed around 21 years, reflecting the maturation of the central nervous system in normally developing individuals. Therefore, this study challenges the assumption surrounding the use and validity of executive functions as a measure of football performance potential in high performing athletes. Highlights: A mixed longitudinal sample of 1018 observations in 343 high level football players. Age rather than experience represents the biggest contributor to EF development. The developmental trajectories of high-level athletes mirror the general population. A threshold effect may help to explain the large within group variance of EF. Different clustering of groups may provide more insight on the role of EF in sport.